Different Paths, One Character: How the Love-Based Curriculum Forms Nationalist-Religious Character - Siti Kamilah; Rita Sriayu; Noor Malihah; Ferli Septi Irwansyah; Artika Eka Prihatini; Fitra Elnurianda (Al-Qalam Institute, 2026)
Madrasah in Indonesia carry a growing responsibility to form pupils whose religious devotion and national commitment develop as one, a task made harder by rising intolerance and thinning empathy among the young. This study examines how the Love-Based Curriculum shapes nationalist-religious character across two contrasting madrasah ibtidaiyah in Balikpapan, one a state madrasah and the other a pesantren-based private school. A qualitative multiple-case design guided the inquiry, drawing on in-depth interviews with principals, teachers, and pupils, participatory classroom observation, and document analysis, with source, technique, and time triangulation securing the validity of the findings. The two schools entered the curriculum through different dimensions of love and different subjects, the first through love of the homeland in Islamic history and the second through love of fellow humans in creed and character. Both nonetheless produced pupils in whom faith and nationhood were fused rather than separated. The analysis shows that a shared affective mechanism, built on teacher exemplarity and a value-laden classroom environment, converted these divergent inputs into a convergent character. From this pattern the study proposes an Affective Convergence Model as its central contribution. The findings imply that madrasah of differing orientation need not adopt an identical program to reach the same formative goal, provided the dimension of love they foreground is carried by an affective pedagogy grounded in the teacher's example.